2007
DOI: 10.1007/s00125-006-0522-y
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein induces phosphorylation of insulin receptor substrate-1 on Ser307 and Ser612 in L6 myocytes, thereby impairing the insulin signalling pathway that promotes glucose transport

Abstract: Aims/hypothesis C-reactive protein (CRP) is associated with insulin resistance and predicts development of type 2 diabetes. However, it is unknown whether CRP directly affects insulin signalling action. To this aim, we determined the effects of human recombinant CRP (hrCRP) on insulin signalling involved in glucose transport in L6 myotubes. Materials and methods L6 myotubes were exposed to endotoxin-free hrCRP and insulin-stimulated activation of signal molecules, glucose uptake and glycogen synthesis were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
72
2
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 54 publications
7
72
2
6
Order By: Relevance
“…In this current study, we, for the first time, demonstrate that hCRP can induce profound insulin resistance in rats in vivo, an effect on the liver but not on the peripheral tissues. In contrast to previous reports that hCRP impairs insulin action in L6 myocytes in vitro, 8 we did not observe an in vivo effect of hCRP on extrahepatic insulin sensitivity. Several factors my contribute to this discrepancy, including differences in hCRP concentration, the time course following hCRP treatment, the use of cell lines in the in vitro study, and, most important, variation in physiological conditions between in vivo and in vitro experiments.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In this current study, we, for the first time, demonstrate that hCRP can induce profound insulin resistance in rats in vivo, an effect on the liver but not on the peripheral tissues. In contrast to previous reports that hCRP impairs insulin action in L6 myocytes in vitro, 8 we did not observe an in vivo effect of hCRP on extrahepatic insulin sensitivity. Several factors my contribute to this discrepancy, including differences in hCRP concentration, the time course following hCRP treatment, the use of cell lines in the in vitro study, and, most important, variation in physiological conditions between in vivo and in vitro experiments.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent in vitro studies have shown that human CRP impairs insulin action in bovine vascular endothelial cells 10 and rat L6 myocytes. 8 However, the effects of hCRP on insulin sensitivity have not been examined in vivo. In this current study, we, for the first time, demonstrate that hCRP can induce profound insulin resistance in rats in vivo, an effect on the liver but not on the peripheral tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In peripheral tissues, both JNK and ERK phosphorylate IRS-1 at Ser307 (rodent equivalent for human Ser312) (Aguirre et al, 2000) and Ser616 (D'Alessandris et al, 2007). The resulting loss of IRS-1 coupling to PI3-K/Akt is predicted to activate another major tau kinase, GSK3␤, which is known to be activated by A␤ (Takashima et al, 1996;Ma et al, 2006;Hu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…IRS-1 contains multiple tyrosine-phosphorylation motifs and they mediate the metabolic and growthpromoting function of insulin [21][22][23]. IRS-1 also contains serine/threonine phosphorylation sites, such as IRS-1-S612, that when phosphorylated results in an inhibition of insulin signaling in the cell [24,25] and may indicate insulin resistance [26].…”
Section: Introductionmentioning
confidence: 99%